Analisis Pertimbangan KPPU terhadap Keterlambatan Notifikasi Akuisisi Saham perspektif Hukum Ekonomi Syariah - Sari, Nurita (Maliyah : Jurnal Hukum Bisnis Islam, 2024)
This study aims to examine the consideration of decisions made by the Business Competition Supervisory Commission (KPPU) related to the Share Acquisition made by PT Matahari Pontianak Indah Mall, from the view of sharia economic law and also the view of positive law. The research method in this study uses normative juridical method, then explained with descriptive method. So that the results of this study provide an understanding that the case in this decision is not considered a violation in the perspective of sharia economic law but juridically the case is still considered to violate the provisions of article 29 of Law number 5 of 1999 which regulates the prohibition of monopolistic practices and unfair business competition.